Inflammation-Related Epigenetic Modification: The Bridge Between Immune and Metabolism in Type 2 Diabetes - Ding, Qiyou; Gao, Zezheng; Chen, Keyu; Zhang, Qiqi; Hu, Shiwan; Zhao, Linhua (Frontiers in Immunology, 2022)
T2DM, as a typical metabolic inflammatory disease, is under the joint regulation of environmental factors and genetics, combining with a variety of epigenetic changes. Apart from epigenetic changes of islet β cells and glycometabolic tissues or organs, the inflammation-related epigenetics is also the core pathomechanism leading to β-cell dysfunction and insulin resistance. In this review, we focus on the epigenetic modification of immune cells’ proliferation, recruitment, differentiation and function, providing an overview of the key genes which regulated by DNA methylation, histone modifications, and non-coding RNA in the respect of T2DM. Meanwhile, we further summarize the present situation of T2DM epigenetic research and elucidate its prospect in T2DM clinical diagnosis and treatment.